Active Transportation, Public Transport And Objectively Measured Meeting Of Physical Activity Guidelines In Adults - Herreros Irarrázabal, Diego (2022)
PURPOSE: This study aimed to examine the associations of active transportation and public transport with the objectively measured meeting of moderate-to-vigorous physical activity (MVPA) and steps per day guidelines in adults by sex from eight Latin American countries. METHODS: Data were obtained from the Latin American Study of Nutrition and Health, a household population-based, multi-national (i.e., Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela), cross-sectional survey from 2524 participants aged 18-65 years. MVPA and steps per day were evaluated using Actigraph GT3X accelerometers. The active transportation (walking and/or cycling; ≥10 min) and mode of transportation (public and private) were collected using self-reported questionnaire. A logistic regression model was used to estimate the odds ratios and 95% confidence intervals for the associations of active transportation (also plus public transport) with meeting vs. not meeting (<150 or ≥ 150 min/week) MVPA guidelines, and meeting vs. not meeting (<7000 or ≥ 7000) steps per day guidelines adjusted for sociodemographic variables. RESULTS: The medians of MVPA and steps per day evaluated by accelerometer were 28.3 (IQR: 16.4-46.4) min/day and 9706.5 (IQR: 6747.8-14018.1). The average time dedicated to active transportation were 12.8 (IQR: 2.8-30.0) min/day. Active transportation (≥10 min) was associated with higher odds of meeting MVPA guidelines (men: OR: 2.01; 95%CI: 1.58-2.54; women: OR: 1.57; 95%CI: 1.25-1.96). These results show greater association when considered active transportation plus public transport (men: OR: 2.98; 95%CI: 2.31-3.91; women: OR: 1.82; 95%CI: 1.45-2.29). Active transportation plus public transport was positively associated with meeting steps per day guidelines only in men (OR: 1.55; 95%CI: 1.15-2.10). CONCLUSIONS: This study supports that active transportation plus public transport is significantly associated with meeting the MVPA and daily steps recommendations. Considering the multiple benefits associated with reducing the levels of private transport in health, society and the environment, promoting and investing in active transportation and public transport should be a priority at the public policy level in Latin America.